Analisis Perkembangan Sosial Ekonomi Peradapan Islam Masa Khulafaur Rasyidin - Adel, Ichsanul Reihan; Wahyudi, Wahyudi; Andrini, Rozi (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
This research discusses the social and economic analysis during the Khulafaur Rasyidin period. The main problem examined is how the policies implemented by Abu Bakar, Umar, Utsman, and Ali impacted the economic development and social stability of the Muslim community. The objective of this study is to analyze and describe the effects of social and economic policies during that era on the establishment of a strong and sustainable Islamic civilization foundation. The method used is a literature study with a descriptive approach, where data is obtained from books, scientific articles, and relevant published documents. The data is systematically analyzed to map the impact of zakat policies, wealth distribution, infrastructure development, and internal conflicts that occurred. The conclusion of this research indicates that the Khulafaur Rasyidin period serves as an important foundation for the development of the Islamic socio-economic system. Although various political challenges and internal conflicts hindered economic growth during Ali's time, the policies of zakat redistribution and administrative reforms implemented by the other caliphs significantly contributed to the social and economic welfare of the Muslim community.